2003
DOI: 10.1007/s00421-002-0759-1
|View full text |Cite
|
Sign up to set email alerts
|

Digit cooling influences grasp efficiency during manipulative tasks

Abstract: A commonly experienced effect of cold is a sensation of numbness and loss of sensibility in the fingers. Intact tactile sensibility of the grasping digits is essential for the efficient scaling of grip force level during the manipulation of hand-held objects. We investigated whether or not cooling of the grasping digits affects scaling of the grip force magnitude in relation to the loads resulting from continuous vertical arm movements performed with a grasped instrumented object. Maxima and minima of load for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
32
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 25 publications
5
32
0
5
Order By: Relevance
“…Moreover, data from studies involving healthy participants with experimentally induced sensory deficits and from patients with sensory loss, because of peripheral nerve damage or central brain lesions, clearly demonstrate the central role of somatosensory feedback for dexterous manipulation. Several methods have been used to transiently interrupt sensory information from the hands of healthy subjects: the use of gloves [6], cooling with sprays or gels [7] and injections of local anaesthetics [8,9]. An almost invariable effect of these manipulations was an increase in the grip force applied against the grasped object.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, data from studies involving healthy participants with experimentally induced sensory deficits and from patients with sensory loss, because of peripheral nerve damage or central brain lesions, clearly demonstrate the central role of somatosensory feedback for dexterous manipulation. Several methods have been used to transiently interrupt sensory information from the hands of healthy subjects: the use of gloves [6], cooling with sprays or gels [7] and injections of local anaesthetics [8,9]. An almost invariable effect of these manipulations was an increase in the grip force applied against the grasped object.…”
Section: Introductionmentioning
confidence: 99%
“…5 The specification was a cuboid in consideration of hand ergonomics. 23 The apparatus had three components: (1) a specially designed steel cuboid (weight ¼ 480 g, 6.0 Â 4.5 Â 9 cm) that provided space for an accelerometer; (2) (Fig.…”
Section: Pinch Devicementioning
confidence: 99%
“…2 Previous researchers demonstrated that impaired control resulted in less precise adjustments in the friction force between the object and finger pulps owing to poor digital sensation by the local anesthesia on the digits or a long-term deprivation of digital sensation. [3][4][5] Any sensory deficit might contribute to permanent impairment, so that complete loss of palmar sensation of these parts is considered a 50% deficit of functional hand capacity. 6 However, few wellcontrolled works or apparati exist to investigate how sensory function contributes to the impairment of hand function.…”
mentioning
confidence: 99%
“…G is modulated during shaking and point-to-point arm movements [2,3,5,27] as well as during locomotion [4]. Local skin anesthesia and digit cooling make the coordination of L and G less precise but does not change the general pattern of coordination [8,32,33]. When people lift an object from a support, they initially exert sufficiently large G force and only after that generate the force in vertical direction necessary to lift the object.…”
Section: Introductionmentioning
confidence: 99%